The Role of Endovascular Intervention in Post Liver Hemorrhagic Blunt Trauma - Rahmad Mulyadi; Prijo Sidipratomo; Indrati Suroyo; Jakub Pandelaki; Sahat Matondang; Krishna Pandu Wicaksono; Heltara Ramandika (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
The liver is the most commonly injured organ in blunt abdominal trauma, and liver trauma is the leading cause of death in abdominal injuries. Liver trauma is associated with high morbidity and mortality, hence thediagnosis and clinical assessment of hepatic trauma play an important role in the management of abdominal liver trauma. Although it is only suitable for patients with stable hemodynamic status, computed tomography(CT scan) is the gold standard for evaluating patients with blunt abdominal trauma, because it can acquire high quality images quickly. For these stable patients, nonsurgical management or endovascular intervention has become the treatment of choice in the majority of liver injuries.